Coupling algorithm of cavity expansion theory and finite element for penetrating reinforced concrete - Huang, Chenglong; Wang, Zhenqing; Li, Shutao; Chen, Yeqing; Dai, Mengnan; Wu, Wei; Wei, Wanli; Gao, Jiazheng; Yang, Qingyuan (Engineering fracture mechanics, 2024)
•Developing a coupling algorithm of cavity expansion theory and finite element for penetrating reinforced concrete.•Presenting two methods for implementing the coupling algorithm in the display dynamics software.•Compared to the finite element method, the algorithm exhibits superior computational stability and efficiency.•The algorithm shows low sensitivity to grid size, and achieves both high precision and rapid computation with small mesh.•This algorithmic framework is applicable to any display dynamics software and has great application value. Aiming at the dynamic problem of projectile penetrating reinforced concrete, this paper creatively proposes a coupling algorithm combining cavity expansion theory and the finite element method. This approach effectively resolves the problem of low efficiency in finite element simulations while ensuring computational accuracy. In this study, based on the cavity expansion theory, we have redeveloped the display dynamics software. Radial stress in the concrete is applied to the warhead surface in the normal direction, and the interaction between the projectile and the steel bar is simulated using the finite element contact algorithm. A coupling algorithm has been developed that can stably and quickly simulate the penetration of reinforced concrete by a projectile. The study indicates that the implementation of the coupling algorithm primarily includes four steps: model establishment and meshing, stress load program design, load application, and initial condition setting. Through verification and analysis, the coupling algorithm presented in this paper is demonstrated to effectively compute the dynamic response of a projectile during penetration. It exhibits superior computational stability and speed compared to the finite element method, and shows minimal sensitivity to grid size. When applied to numerical models with small meshes, it achieves both high precision and rapid computation. The coupling algorithm program design proposed in this paper can be implemented in any display dynamics software, offering a robust approach for engineers and researchers to predict projectile penetration effects. Furthermore, it provides a rapid assessment method for the anti-penetration performance of reinforced concrete structures.